Practical rationality for poverty mitigation policies – A contrast between Onora O'Neill and Alasdair MacIntyre - Rocha, Rafael Carneiro (DoisPontos, 2023)
In this article, we will present the contrast between the epistemic aspects of an approach that we will conveniently call - and not from a rigorous historical pretension – “Aristotelian”, such as that of Alasdair MacIntyre, and epistemic aspects of an approach that we will also conveniently call “Kantian”, such as that of Onora O'Neill. Our hypothesis is that the presentation of these different perspectives, in terms of practical rationality for the formulation of poverty mitigation policies, would allow us to verify that the Aristotelian approach is contextually efficient, while the Kantian approach is universally demanding. However, if we take into account that a certain international political and economic conjuncture makes poverty mitigation difficult, the addressing of this problem would need to occur in a globally efficient and universally demanding manner. In this sense a Kantian theory of obligation seems to provide epistemic requirements necessary for the formulation of efficient policies.